2021
DOI: 10.1186/s42269-021-00590-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and anxiety symptoms in Egyptian children and adolescents during COVID-19 pandemic lockdown

Abstract: Background Coronavirus Disease Pandemic 2019 has a pervasive effect on all health aspects include psychological and mental health. This study aimed to assess the hidden stressful impact of COVID-19 pandemic on Egyptian children and adolescents’ lifestyles 2 months after lockdown in Egypt by detecting symptoms of anxiety and sleep disorders. Online questionnaire was used by snowball sampling approach 2 months after lockdown targeting children and adolescents. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…Sleep behaviours are also known to have altered [ 27 ], with 54% of children reported to show sleep disturbance during lockdown. Specific associations between changes in sleep behaviour and increases in anxiety having been demonstrated in Italy [ 28 ], Egypt [ 29 ] and Spain [ 30 ], according to parent report.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep behaviours are also known to have altered [ 27 ], with 54% of children reported to show sleep disturbance during lockdown. Specific associations between changes in sleep behaviour and increases in anxiety having been demonstrated in Italy [ 28 ], Egypt [ 29 ] and Spain [ 30 ], according to parent report.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2020) reported that the prevalence of depressive and anxiety symptoms among the 12 to 18-year-old Chinese youth was 43.7% and 37.4%, respectively. Sleep disturbances were also present among children during the pandemic (problems initiating and maintaining sleep: 33.4% of the children studied, excessive sleepiness: 15.7%; (El Refay et al, 2021).…”
Section: Schoolchildrenmentioning
confidence: 99%
“…In children and adolescents, an investigation with 765 participants aged 4–16 years conducted by Refay et al found that 65.6% showed symptoms suggestive of a sleep disorder, as measured by the Sleep Disturbance Scale for Children score (SDSC) [ 7 ]. Almost 16% of the children suffered from EDS, with significant positive correlations between SDSC scores and increased screen usage.…”
Section: Covid-somnia the Impact Of Home Confinement And Cns Hypersom...mentioning
confidence: 99%
“…Most studies about sleep during the COVID-19 pandemic in this population address insomnia, psychological symptoms, and the impact of disrupted sleep–wake schedules [ 6 8 ]. Disorders related to initiating and maintaining sleep being more common, and it is estimated that around 16% in a group of Egyptian children experienced EDS during the pandemic [ 7 ]. Studies during the COVID-19 pandemic suggested that children’s sleep duration increased with a transition to circadian phase delay [ 6 ].…”
Section: Introductionmentioning
confidence: 99%